The determinants of the voting premium in Italy: The evidence from 1974 to 2003 - Caprio, Lorenzo; Croci, Ettore (Journal of Banking & Finance, 2008)
We examine the voting premium in Italy in the period 1974 to 2003, when it ranged from 1% to 100%. At firm level, the measure of the price differential between voting and non-voting stocks cannot be fully explained without taking into account the effect of the largest shareholder’s identity. Family-controlled firms have higher voting premiums, especially when the family owns a large stake in the company’s voting equity and the founder is the firm’s CEO and/or Chairman. We explain this result by showing that families attach greater importance to control and are more prone than other types of controlling shareholders to expropriate the non-voting class of shareholders.